TECHNOLOGY INTEGRATION IN PHILIPPINE HIGHER EDUCATION: A CONTENT-BASED BIBLIOMETRIC ANALYSIS - Cadiz, Ma. Catalina D.; Manuel, Lalaine Ann F.; Reyes, Mercedita M.; Natividad, Lexter R.; Ibarra, Florante P (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
The penetration of technological advancements into higher education institutions is a multifaceted phenomenon influenced by diverse considerations. This paper breaks new ground by conducting a content-based bibliometric analysis of technology integration within Philippine Higher Education Institutions (HEIs). Employing a systematic five-step approach, the study meticulously navigates the bibliometric landscape, encompassing database identification, scope determination, article refinement, compilation, and analysis. A corpus of 61 articles sourced from the Google Scholar database spanning the period from 2012 to 2022 constitutes the focal point of bibliometric scrutiny. Delving into the thematic analysis, the study unveils a rich tapestry of insights encapsulated in five overarching themes: Technology, Industrial Revolution 4.0, and Education 4.0; Higher Education and Digital Technology; Educational Philosophies in the New Normal Higher Education Setting; Transformation of Technology Education in Higher Education and the Academics; and Higher Education, Technology, and the Learners. The findings underscore the imperative of aligning educational paradigms with the imperatives of Industrial Revolution 4.0, offering a blueprint for navigating the new normal in higher education. By elucidating the intricate interplay between technology and pedagogy, this research not only enriches scholarly discourse but also provides practical insights for HEIs seeking to embrace technological innovation in fostering academic excellence and resilience amidst evolving educational landscapes.